Assessment of malaria prevention knowledge, attitude, and practice and associated factors among households living in rural malaria-endemic areas in the Afar Pastoral Region of Ethiopia - Addis, Desalegne; Gebeyehu Wondmeneh, Temesgen (Frontiers in Public Health, 2023)
Background Malaria morbidity has reduced significantly in most regions of Ethiopia, but it is still a serious issue in the northeast, particularly in the Afar region. Objective The study aimed to evaluate household heads' knowledge, attitudes, and practices toward malaria prevention and its associated factors in rural Ada'ar woreda district in the Afar region. Methods A community-based cross-sectional study was conducted among 422 households living in Ada'ar woreda district. A systematic sampling technique was used to select households. A pre-tested, structured questionnaire was used to interview randomly selected adult household heads. Frequency and percentage were computed. Logistic regression was used to determine the association between independent and dependent variables. Statistical significance was considered to be a p-value <0.05. Results Nearly two-thirds (64.2%) of household heads had good knowledge of malaria prevention, and 46.9% had a positive attitude toward it. About 17.3 and 56.9% of study participants had good malaria prevention practices and good healthcare seeking behaviors, respectively. Illiterate (AOR = 2.62, 95% CI: 1.49–4.63) and low-income (AOR = 2.6, 95% CI: 1.2–5.6) participants were more likely to have poor knowledge of malaria prevention (malaria signs and symptoms, malaria transmissions, and malaria prevention methods). Married participants (AOR = 2.52, 95% CI: 1.02–6.29) and illiterates (AOR = 2.83, 95% CI: 1.69–4.73) had negative attitudes toward malaria prevention. Household heads with poor knowledge of malaria prevention had 85% higher rates of practicing poor malaria prevention methods (regular bed nets used; AOR = 1.85, 95% CI: 1.2–2.8). Young adults (18–25 years) were more likely to have poor healthcare seeking behaviors (AOR = 3.5, 95% CI: 1.73–7.1), while pastoralists had a lower likelihood (AOR = 0.46, 95% CI: 0.28–0.8). Conclusion Knowledge, attitude, and practices toward malaria prevention remain a problem in malaria-endemic rural areas of the Afar region of Ethiopia. There is a need for the implementation of interventions that will focus on increasing knowledge of malaria prevention and encouraging positive attitudes toward it, as well as promoting regular bed net usage and healthcare seeking behaviors.